New Insights of CCR7 Signaling in Dendritic Cell Migration and Inflammatory Diseases - Hong, Wenxiang; Yang, Bo; He, Qiaojun; Wang, Jiajia; Weng, Qinjie (Frontiers in Pharmacology, 2022)
CCR7, collaborated with its ligands CCL19 and CCL21, controls extensive migratory events in immune system. CCR7-bearing dendritic cells can swarm into T cell zones in lymph nodes, initiating the antigen presentation and T cell response. Abnormal expression of CCR7 in dendritic cells will cause a series of inflammatory diseases due to the chaotic dendritic cell trafficking. In this review, we take an in-depth look at the structural-functional domains of CCR7 and CCR7-bearing dendritic cells trajectory to lymph nodes. Then we summarize the regulatory network of CCR7, including transcriptional regulation, translational and post-translational regulation, internalization, desensitization, and recycling. Furthermore, the potential strategies of targeting CCR7 network to regulate dendritic cell migration and to deal with inflammatory diseases were integrated, which not only emphasizes the possibility of CCR7 to be a potential target of immunotherapy, but also has an implication on the homing of dendritic cells to benefit inflammatory diseases.